The Urgency of Sex Education for Adolescents in the Islamic Religious Education Paradigm - Himmatul Ulya Nur; Bernika Irvandianis Ifadah; Ita Sunfiana; Nur Sa'diyatus Syafa'ah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Education is an important part of human life. One of them is sex education which is still very taboo given to every individual. The lack of understanding of adolescents regarding sex education causes many sexual deviations to occur and are carried out by adolescents. For this reason, the urgency of sex education must be given to adolescents in accordance with Islamic religious teachings. The purpose of this research is to find out the urgency of sex education given to adolescents according to the paradigm of Islamic education. This research uses a qualitative approach and a descriptive research type, with a case study at MTs Muhammadiyah 20 Menongo. Methods of data collection using the method of observation, interviews, and documentation. The collected data is then analyzed through: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results of this study are: 1) The urgency of providing Islamic sex education to adolescents, namely as an effort to prevent free sex behavior among adolescents; efforts to prevent the impact of free sex behavior such as pregnancy out of wedlock, various sexual diseases and sexual violence; and efforts to instill behavior in adolescents that are in accordance with nature as men and women. 2) The role of Islamic Religious Education Institutions is to provide a good environment for the development of adolescents; provide a basis for behaving in accordance with the teachings of the Islamic religion; become a source of good and correct knowledge information, especially related to sex education. 3) Strategies in providing sex education material, namely providing advice or understanding regarding Islamic sex education in every religious activity; using learning media; as well as strictly implementing the rules that already exist in school institutions, especially related to immoral acts and sexual deviations.